Common arterial trunk and ventricular non-compaction in Lrp2 knockout mice indicate a crucial role of LRP2 in cardiac development - Baardman, Maria E. (Dis Model Mech, 2016)
Lipoprotein-related receptor protein 2 (LRP2) is important for development of the embryonic neural crest and brain in both mice and humans. Although a role in cardiovascular development can be expected, the hearts of Lrp2 knockout (KO) mice have not yet been investigated. We studied the cardiovascular development of Lrp2 KO mice between embryonic day 10.5 (E10.5) and E15.5, applying morphometry and immunohistochemistry, using antibodies against Tfap2α (neural crest cells), Nkx2.5 (second heart field), WT1 (epicardium derived cells), tropomyosin (myocardium) and LRP2. The Lrp2 KO mice display a range of severe cardiovascular abnormalities, including aortic arch anomalies, common arterial trunk (persistent truncus arteriosus) with coronary artery anomalies, ventricular septal defects, overriding of the tricuspid valve and marked thinning of the ventricular myocardium. Both the neural crest cells and second heart field, which are essential for the lengthening and growth of the right ventricular outflow tract, are abnormally positioned in the Lrp2 KO. This explains the absence of the aorto-pulmonary septum, which leads to common arterial trunk and ventricular septal defects. Severe blebbing of the epicardial cells covering the ventricles is seen. Epithelial-mesenchymal transition does occur; however, there are fewer WT1-positive epicardium-derived cells in the ventricular wall as compared to normal, coinciding with the myocardial thinning and deep intertrabecular spaces. LRP2 plays a crucial role in cardiovascular development in mice. This corroborates findings of cardiac anomalies in humans with LRP2 mutations. Future studies should reveal the underlying signaling mechanisms in which LRP2 is involved during cardiogenesis.